Optimalisasi Nilai Kejujuran Anak Usia Dini Melalui Bercerita Dengan Papan Flanel Pada Anak Kelompok A Di Tk Putra Bangsa Jatikuwung, Karanganyar Tahun Ajaran 2014/2015 - Mustaqim, Muh Saiful; , Dra. Aryati Prasetyarini, M.Pd (2016)
The purpose of this study is to optimize the value of honesty on children through storytelling using flannel board. This study was designed with classroom action research (CAR) in which each cycle consisted of planning, implementation, observation, and reflection. This study was a callaborative between researchers and classrom teachers. Data were collected through observation, documentation, and interview. The subject of this research was kindergarten children in group A Putra Bangsa Kindergarten Jatikuwung, Gondangrejo, Karanganyar academic year 2014/2015. The data analysis was done by using data collection, data reduction, data presentation, and conclusion. The results indicated that in had been optimization of the value of honesty of children through storytelling with fannel board in group A Putra Bangsa Kindergarten Jatikuwung. This was demonstrated by the acquisition of the results of the two cycles that had been implemented. Optimizing the value of honesty in this study could be seen on the achievement of indicators that had been assigned a value honesty of children indicating the category growing as expected respectively (cycle I and II) 71% and 100% with an average value af class (cycle I and II) 61,3% and 71,8%. In the second cycle, the student achievement indicator had been reached. The conclusion of this study was to optimize the value of honesty of children in grup A Putra Bangsa Kindergarten Jatikuwung year 15 could be done through storytelling with flannel board.